Hand Grip Strength as A Potential Nutritional Assessment Tool in Long-Term Care Homes - Susan, J Whiting; Pui, Chi Cheng; Lilian, Thorpe; Navita, Viveky; Jane, Alcorn; Thomas, Hadjistavropoulos; Wendy, J. Dahl (Journal of Aging Research And Healthcare, 2016)
Loss of muscle mass and functionality leads to increased risk for falls and onset of frailty, especially residents of long term care (LTC) homes. Hand grip strength (HGS) is emerging as a promising tool to measure muscle strength and a proxy for functionality. Given its promise as a screening tool, several studies report cut-offs below which measured strength was predictive of risk of poor mobility in older subjects. A scoping review was conducted to examine whether HGS was currently being used in LTC, as studies demonstrate hand grip strength as positively correlated with activities of daily living, implying increased dependence on caregivers including mealtimes. Of 19 published studies in 2015, only two report HGS use. As there is an association of grip strength with nutrition-related outcomes, hand grip strength should be used as part of nutritional assessment by dietitians in LTC, as poor muscle strength adversely affects activities of daily living that may impact intake.
Keywords: hand grip strength; nutritional status; older adults; long term care.